Agile-Based Integrated Community Information System With Marketplace Feature: Empirical Evaluation In The Papuan Student Community Of Sriwijaya (Kompas) - TIPRAN YIKWA TISJANDT; Edi Surya Negara (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2025)
Papuan students in South Sumatra face challenges related to fragmented communication, limited information accessibility, and low participation in organizational activities. The absence of an integrated digital platform has reduced coordination efficiency within the Papuan Student Community of Sriwijaya (KOMPAS). This study aims to design and empirically evaluate an Agile-based integrated web information system incorporating digital governance and marketplace features to enhance organizational performance and engagement. The system was developed using the Agile methodology through five iterative sprints over a ten-month period involving 15 organizational stakeholders and 75 active members. The platform was implemented using Laravel and MySQL within a three-tier architecture framework. Evaluation procedures included functional testing, performance analysis, and usability assessment using the System Usability Scale (SUS). The results indicated an average page load time of 1.2 seconds (desktop) and 2.8 seconds (mobile), with a PageSpeed score of 94 and 85% unit test coverage. The system achieved a SUS score of 82.5, categorized as excellent usability. After one month of implementation, information accessibility increased from 24% to 76%, participation rose from 38% to 62%, and member engagement improved from 31% to 73%. The marketplace module recorded 23 transactions totaling Rp 8,500,000. These findings demonstrate that integrating digital governance mechanisms with marketplace functionality significantly enhances coordination, engagement, and economic participation in student-based community organizations.